Early-Life Stress and Adult Inflammation. (August 2014) - Fagundes, Christopher P.; Way, Baldwin
The origins of modern psychology are deeply rooted in the notion that stressful early-life experiences negatively impact people's mental health. Emerging work in the field of health psychology suggests that early-life stress also impacts physical well-being. Indeed, those who experienced severe early-life stress as children are more at risk for cardiovascular disease, type 2 diabetes, and cancer compared with those who did not have those early-life experiences. Recent work in the field of psychoneuroimmunology suggests that inflammation may be one mechanism underlying these associations. In this article, we provide a brief overview of the literature on early-life stress and inflammation and how psychological, autonomic, neuroendocrine, and epigenetic responses to the early environment lead to potentiated inflammation in adulthood. We conclude by highlighting the need for health-promotion and disease-prevention programs that are designed to reduce the frequency and severity of early-life stress.